Neutrophil to lymphocyte ratio at diagnosis can estimate vasculitis activity and poor prognosis in patients with ANCA-associated vasculitis: a retrospective study - Sung Soo Ahn; Seung Min Jung; Jason Jungsik Song; Yong-Beom Park; Sang-Won Lee (BMC Nephrology, 2018)
Abstract Background Neutrophil to lymphocyte ratio (NLR) was introduced to predict poor prognosis in various diseases, but not all variants of ANCA-associated vasculitis (AAV). In this study, we aimed to investigate whether NLR at diagnosis can estimate vasculitis activity at diagnosis and poor prognosis during follow-up in patients with AAV. Methods We retrospectively reviewed the medical records of 160 patients with AAV. We collected clinical and laboratory data at diagnosis and obtained remission and death as poor prognosis. We stratified AAV patients into three groups according to tertile and defined the lower limit of each highest tertile as the optimal cut-off (5.9 for NLR and 15.0 of Birmingham vasculitis activity score [BVAS] for severe AAV). Results The mean age at diagnosis was 55.2 years and 48 patients were men. In the univariable linear regression analysis, BVAS was negatively correlated with lymphocyte count and positively correlated with erythrocyte sedimentation rate (ESR), C-reactive protein (CRP) and NLR. In the multivariable linear regression analyses of ESR and CRP with either lymphocyte count or NLR, lymphocyte count (β = − 0.160) and NLR (β = 0.169) were associated with BVAS. Patients having NLR ≥ 5.9 exhibited severe AAV more frequently than those having NLR < 5.9 at diagnosis (relative 2.189, P = 0.023). Patients having NLR ≥ 5.9 exhibited a higher frequency of AAV relapse, but not death, than those having NLR < 5.9 (P = 0.016). Conclusions NLR at diagnosis can estimate vasculitis activity at diagnosis and predict relapse during follow-up in patients with AAV.